Sterilization of Medical Equipment by Plasma Technology - Norrapon Vichiansan (Science Faculty of Chiang Mai University, 2019)
This study examined sterilization of scalpels using plasma technology by comparing the performance effectiveness of two techniques, plasma solution (PS) and plasma dielectric barrier discharge (PDBD), on Escherichia coli and Staphylococcus aureus at 0.5 McFarland. The experimental design was used to determine the optimal condition for both the techniques to be 100% effective by using the ten-fold dilution spread plate count. For PS, the voltage was set at 520 V for 20 s and the concentration of sodium acetate was 1 g/L. For PDBD, the distance between the anodes was 9.4 mm; the discharge time was 14 min; the power was 76 W; and the argon gas flow rate was 22 L/min. On comparing the time taken for 100% sterilization by the two techniques, it was found that PS used less time than PDBD. However, upon testing with Optical Emission Spectrometry (OES), the hydroxyl free radicals produced by PDBD were observed to be greater than those produced by PS.